Community Readiness to Prevent Opioid Overdose - Ringwalt, Christopher (Health Promot Pract, 2018)
Effective community-based actions are urgently needed to combat the ongoing epidemic of opioid overdose. Community readiness (CR) has been linked to communities’ support for collective action, which in turn has been associated with the success of community-wide prevention strategies and resulting behavior change. Our study, conducted in North Carolina, assessed the relationship between CR and two indices of opioid overdose. County-level data included a survey of health directors that assessed CR to address drug overdose prevention programs, surveillance measures of opioid overdose collected from death records and emergency departments, and two indicators of general health-related status. We found that counties’ rates of CR were positively associated with their opioid-related mortality (but not morbidity) and that this relationship persisted when we controlled for health status. North Carolina counties with the highest opioid misuse problems appear to be the most prepared to respond to them.